Exploring feminism in midwifery and maternity research: A scoping review - Peters, Mirjam C.E.; Froehlich, Marie L.; Zinsser, Laura A. (Sexual & reproductive healthcare, 2025)
The intersection of midwifery, maternity care, and feminist theory remains underexplored, particularly regarding its prevalence, contexts, and potential benefits for midwifery science. Feminist perspectives address sociocultural, economic and political factors at both individual and structural levels. In health care, these factors significantly influence women’s health. Feminist perspectives offer approaches to better understand gendered experiences, address systemic inequalities, and gain deeper insights into sociocultural, economic and political dynamics. The aim is to show how feminist perspectives are incorporated into midwifery research and how they are used. A PRISMA-ScR-guided scoping review was conducted with systematic searches in Medline, MIDIRS, CINAHL, and SocINDEX, in December 2023. Studies over the last decade in English and German with the keyword “feminism” in midwifery and maternity care were included. Data were extracted and summarized descriptively. Patterns and underlying discourses were identified through iterative process to identify underlying themes. From 1,523 records, 246 studies were included. These studies utilized feminist frameworks such as intersectional feminism, post-structural feminism, and feminist critical theory. Many studies focused on marginalized groups. Themes addressed included the experiences of women and families, healthcare needs, societal norms, ethical considerations, information and decision-making, and the role of technology. Feminist perspectives emphasize and contextualize the needs of women and marginalized groups, highlighting societal influences on health while providing approaches to analyse gender dynamics, power relations, and systemic inequalities. This study highlights the potential for integrating feminist perspectives into midwifery science to develop more nuanced and equitable approaches to maternity care.